Novelty in Multidisciplinarity - Abeer M. Refky M. Seddeek (Insights into Language, Culture and Communication, 2021)
The launch of Insights into Language, Culture and Communication (ILCC) by the Academy Publishing Center (APC) is a recognition that multi-disciplinarity not only shapes the social landscape of language, culture and communication but also establishes a significant and dynamic area of investigation in contemporary communication and interaction. More specifically, the journal marks an important shift in the status of multidisciplinarity theoretically, methodologically, and empirically carving new routes through several disciplinary terrains to consolidate and advance the development of linguistics, culture and media scholarship. What makes ILCC stand out among recently emerging journals is that it serves as an international forum for the growing body of works in several interlocking disciplines, engages in critical discussions of key contemporary challenges arising from the scale and speed of new media development, and opens up an entirely new line of research premised on a wide range of disciplinary perspectives. ILCC encourages submissions from a wide range of disciplines such as: philosophy, sociology, linguistics, applied linguistics, literary studies, cultural studies, critical theory, media studies, gender studies and the visual arts, all of which assist scholars to shoehorn their multidisciplinary arguments.